1985
DOI: 10.1099/00221287-131-3-459
|View full text |Cite
|
Sign up to set email alerts
|

Partial Purification and Some Properties of an Aromatic-amino-acid and an Aspartate Aminotransferase in Brevibacterium linens 47

Abstract: An L-aromatic-amino-acid aminotransferase (AT-IA) and an L-aspartate aminotransferase (AT-IB) were partially purified from Brevibacterium linens 47 grown on L-phenylalanine as sole nitrogen source and some properties were examined. Both enzymes were active with L-aromatic amino acids and L-aspartate. AT-IA showed 6 to 12 times higher affinity and slightly higher V,,, for the aromatic amino acids than for aspartate. AT-IB had higher affinity for tryptophan and tyrosine than for aspartate. However, this enzyme s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
1
16
1
Order By: Relevance
“…This two-step metabolic sequence has been demonstrated in lactococci (17). An aminotransferase has been identified in Lactococcus lactis (32), and two aminotransferases have been partially purified from B. linens (21). In Saccharomyces cerevisiae, the genes encoding aminotransferase in the genome fall into the following three groups: (i) ScAAT1 and ScAAT2, encoding aspartate amino acid aminotransferases (11,23,29); (ii) ScBCA1, encoding a branched-chain amino acid aminotransferase (15); and (iii) ScARO8 and ScARO9, encoding aromatic amino acid aminotransferases (20,28).…”
mentioning
confidence: 99%
“…This two-step metabolic sequence has been demonstrated in lactococci (17). An aminotransferase has been identified in Lactococcus lactis (32), and two aminotransferases have been partially purified from B. linens (21). In Saccharomyces cerevisiae, the genes encoding aminotransferase in the genome fall into the following three groups: (i) ScAAT1 and ScAAT2, encoding aspartate amino acid aminotransferases (11,23,29); (ii) ScBCA1, encoding a branched-chain amino acid aminotransferase (15); and (iii) ScARO8 and ScARO9, encoding aromatic amino acid aminotransferases (20,28).…”
mentioning
confidence: 99%
“…It has been suggested that in the oenological bacterium Oenococcus oeni, the transamination of L-methionine is the first step in the pathway for degradation of L-methionine to VSCs (16). In B. linens, one aromatic amino acid aminotransferase and one aspartate aminotransferase were partially purified and characterized (11), but neither of these enzymes was tested with L-methionine as the transamination substrate. A transamination pathway was also suggested for several cheese-ripening yeasts, including G. candidum (7), as well as for the brewing yeast Saccharomyces cerevisiae (15), and this pathway could be involved in VSC production in such microorganisms.…”
mentioning
confidence: 99%
“…High activities toward dicarboxylic substrates characterized also ArATs isolated from other sources. The activity of ArAT from Escherichia coli toward l -aspartate reached 65 % of the maximum activity determined with l -tyrosine (Powell and Morrison 1978), and activity of ArAT from Brevibacterium linens toward l -aspartate reached 50 % of the maximum activity determined with l -phenylalanine (Lee and Desmazeaud 1985). For comparison, aspartate aminotransferases studied in parallel with ArATs by Powell and Morrison (1978) and Lee and Desmazeaud (1985) were characterized by considerably different relative activities toward amino acid substrates.…”
Section: Resultsmentioning
confidence: 99%